Control of Bidirectional DC-DC Converter with Proportional Integral Derivative - Septiawan, Fadlilah Reza; Tahtawi, Adnan Rafi Al; Ilman, Sofyan Muhammad (Peneliti Teknologi Teknik Indonesia, 2024)
In the bidirectional DC-DC converter (BDD converter), power flow is created in two directions. The topology of the converter has two modes: discharge mode and charge mode. In this discussion, control for both modes is done using an external switch. This study discusses points for planning a bidirectional DC-DC converter using the MATLAB / Simulink application and implementing equipment using PID control embedded in the Arduino UNO-type microcontroller device. The converter design in the MATLAB / Simulink application with two modes uses PID control, however, the PID method can only be done in discharge mode in the experimental stage. In obtaining PID parameters using Ziegler-Nichols tuning 1. The response results have been designed in the MATLAB / Simulink application for both modes, which have a rise time value of less than 0.2 seconds, a settlement time value of less than 1 second, and a steady-state error of less than 2%. The results of the hardware experiment in discharge mode have a rise time value of 1 second, a settlement time of 2 seconds, and a steady-state error of 0.8%. The hardware experiment response is slower than the simulation, and the steady state error is larger than the simulation. The charging method can be carried out with a current value of -0.1A.